EDUKASI DAN PELATIHAN TERKAIT MEKANISME KOPING YANG ADAPTIF BAGI PERAWAT PELAKSANA IGD DALAM MENGHADAPI STRES KERJA - Rahmat Ali Putra Harahap; Khairunnisa Batubara (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Work stress is a common phenomenon in the Emergency Department (ER) environment of hospitals that has an impact on the mental health and performance of nurses. This community service aims to provide education and training related to adaptive coping mechanisms for nurses implementing the ER in dealing with work stress. This activity was carried out at the Regional General Hospital (RSUD) Doloksanggul in May 2025 using counseling methods, group discussions, and relaxation technique training. The results of the activity showed an increase in participants' understanding of the types of work stress and effective coping strategies, such as problem-focused and emotion-focused coping. Evaluation was carried out through pre-tests and post-tests as well as observations of participant involvement in the discussion. The increase in knowledge scores and positive feedback from participants showed that this activity was useful and could be implemented in the work unit. It is hoped that similar activities can continue to be carried out to improve the psychological well-being of nurses.